The culture of election and democracy in the taxonomy of Islamic political literature in relation to the democratic revolutions in the Middle East and North Africa - Shuriye, Abdi Omar (Canadian Center of Science and Education, 2012)
This research is an attempt to study the process of election in the spectrum of formal democracy within the Islamic polity in relation to the current democratic revolutions in the Middle East and North Africa. The objective of this research is to comprehensively assess the process of election and democratic compatibility with Islamic norms within the taxonomy of Islamic political literature in relation with democratic revolutions in the Middle East and North Africa. The research utilized library-based methodology to arrive at comprehensive conclusions. The significance of this study lies on the fact that it contributes to a timely issue which attracts academic and political attention. The research makes calculated predictions and provides answers to current concerns of political interest.